Structural Variability of 3C 111 on Parsec Scales - Grossberger , C.; Kadler , M.; Wilms , J.; Müller , C.; Beuchert , T.; Ros , E.; Ojha , R.; Aller , M.; Aller , H.; Angelakis , E.; Fuhrmann , L.; Nestoras , I.; et al. (České vysoké učení technické v Praze, 2012)
We discuss the parsec-scale structural variability of the extragalactic jet 3C111 related to a major radio flux density outburst in 2007. The data analyzed were taken within the scope of the MOJAVE, UMRAO, and F-GAMMA programs, which monitor a large sample of the radio brightest compact extragalactic jets with the VLBA, the University of Michigan 26 m, the Effelsberg 100 m, and the IRAM 30m radio telescopes. The analysis of the VLBA data is performed by fitting Gaussian model components in the visibility domain. We associate the ejection of bright features in the radio jet with a major flux-density outburst in 2007. The evolution of these features suggests the formation of a leading component andmultiple trailing components
Keywords: galaxies; individual; 3C111 – galaxies; active – galaxies; jets– galaxies; nuclei